ANALISIS VARIABEL SOSIAL, EKONOMI, DAN DEMOGRAFI YANG MEMPENGARUHI MOBILITAS ULANG ALIK DI KOTA PEKANBARU - Tauqifi, Muhamad; Yusni, Maulida; Nobel, Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of Social, Economic, and Demographic Variables on Reflective Mobility to Pekanbaru City. This research was conducted in Pekanbaru City, to people who do shuttle mobility or commuting to Pekanbaru on the same day. The research method used is descriptive quantitative research method. The object this research is people who do reflective mobility in Pekanbaru on the same day. The population in this study amounted to 5572 people. While samples taken were 98 people used probability sampling and data collection methods using questionnaire. The results of this study indicate that 1) social variables consisting of education level, economic variables consisting of monthly income and marital status have significant effect on reflective mobility in the city of Pekanbaru. while demographic variables consisting of the number of dependents has no significant effect on reflective mobility in the city of Pekanbaru.Keywords: Social, Economic, Demographic, and Return Mobility Variables in Pekanbaru City